Гидромалакофауна окрестностей города Костромы, озера Плещеева и реки Нерль (Волжская) - Затравкин, М.Н. (Вестник зоологии, 1975)
Species composition and zoogeographic structure of molluscs from the environs of Kostroma, Lake Pleshcheev and the river Nerl (Volgian) are presented. Background species are marked, a list of species with indication of habitats (collections of 1971) is given.